Remote sensing and geology in the Bojuru region, middle portion of the Coastal Plain of Rio Grande do Sul State, Brazil: Boundaries of the Pleistocene and Holocene barriers and the forms of land use. - Hansen, Marco Antonio Fontoura (2021)
In the locality of Bojuru, the middle portion of Rio Grande do Sul coastal plain (Southern Brazil) the research was carried out with the purpose of a better understanding the geology, geomorphology, recognition of the sedimentary facies of this coastal area, and ways of land use and occupation. This region has active coastal sedimentation, with several occurrences and research for heavy minerals, mainly ilmenite (FeTiO3). For the stage of digital processing of satellite images, generation of databases, and crossing of information, the software SPRING 5.2.7-INPE, was used. The objective of this study aimed to verify how coastal sedimentary environments, due to their morphology and associated facies, directly or indirectly influence land use and occupation of the locality of Bojuru, on the middle coast of Rio Grande do Sul State. The techniques used in the digital image processing of the 1 MSS, 2 MSS, 7 ETM+, and three 8 OLI Landsat satellites, orbit 221/82, with their passage years being 1973, 1980, 2002, 2016, and 2019. The result of this processing with the field truths resulted in the delimitation of the main features related to coastal evolution, based on the spectral combination of the bands 742-RGB of the Landsat 8 OLI of 2019. In this way, it was possible to delimit the features of the Pleistocene, Lagoon, and Holocene barriers in the evolution of coastal and sedimentation dynamics. The highlights made, in the false color, were through the arrangement of the bands 543-RGB on the satellite image which favored the identification of the forms of land use and occupation and highlighted the morphostratigraphic changes of the Pleistocene and Holocene barriers deposits. Therefore, the greatest contrast was observed between the emerged and submerged portion, highlighting the sand/sea limit, the limit between the Pleistocene and Holocene barriers. The forms of use and occupation were also highlighted, enhancing the vegetation on the dunes and cultivation areas, with a loss of 61.2% in the dune area in 46 years.